English Segmental Pedagogy, Homophonic Realisation And Communicative Competence In L2 - Julianah Ajoke Akindele; Victor Ayomide Fabunmi (The Journal of Studies in Language, Culture and Society, 2024)
The study investigates and compares the performance of two groups of final year English major undergraduates of a Nigerian University in the production and perception of homophones. One group consisting of twenty students were taught the English sound segments with the use of an e-learning software while the second group of twenty students were taught the segmentals without the use of the software. Each of the participants read aloud a sentences containing homophones and also participated in a dictation test. The collected data was analysed perceptively and acoustically using the sound analytical tool, PRAAT developed by Paul Boersma and David Weenick of the University of Amsterdam. Results reveal that students in the first group who were taught with the e-learning software performed better than those in the second group in the production, reception and understanding of homophones. Findings confirm that the use of e-learning software in language pedagogy will play a significant role for improved performance and greater communicative competence in Nigeria. Keywords: Communicative competence, E-Learning, Homophonic realisation, Pedagogy, performance